Urology : Manual of practical classes 4th year students of medical faculties - Gubar, A. O.; Губарь, Андрій Олександрович (Запорізький державний медичний університет, 2021)
In the manual for preparation practical classes, methodological developments for eight topics in the discipline "Urology" according to the work program are collected.